2019
DOI: 10.1021/acs.inorgchem.9b01945
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Synthesis and Crystal Structure of MoC-Type Tungsten Nitride by Nitridation with Ammonium Chloride

Abstract: A novel tungsten nitride, MoC-type WN, was synthesized at 6 GPa and 1200 °C via nitridation of tungsten by ammonium chloride as a nitrogen source. This compound is isostructural with γ′-MoC, which has a hexagonal structure with a space group of P63/mmc (No. 194). Micrometer-sized single crystals of MoC-type WN were grown in molten ammonium chloride flux. In addition, NaCl-type WN and WC-type WN were synthesized via nitridation by ammonium chloride at 6 GPa and 1000 °C. Ammonium chloride is appropriate as a nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…19−21 Facet planes of a crystal can be sometimes controlled by changing flux, and this is also true for crystal growth under high pressure (e.g., hexagonal BN 22 ). Hinted by a recent work on WN single crystals grown at 6 GPa using NH 4 Cl, which acts as a flux as well as a nitrogen source, 23 we attempted to grow TaON single crystals using a NH 4 Cl flux (6 GPa, 1200 °C). In this case, we obtained black rod-shaped crystals, formed as a bundle of thin needles (Figure 1d), where the growth direction is [01−1], as determined from XRD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19−21 Facet planes of a crystal can be sometimes controlled by changing flux, and this is also true for crystal growth under high pressure (e.g., hexagonal BN 22 ). Hinted by a recent work on WN single crystals grown at 6 GPa using NH 4 Cl, which acts as a flux as well as a nitrogen source, 23 we attempted to grow TaON single crystals using a NH 4 Cl flux (6 GPa, 1200 °C). In this case, we obtained black rod-shaped crystals, formed as a bundle of thin needles (Figure 1d), where the growth direction is [01−1], as determined from XRD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The results indicate that mechanical properties generally decrease with an increase of the vacancy concentration, except for the hardness of the WC-type WN, which increases with a vacancy concentration up to 8 at%. Experimentally, Sasaki et al (2019) and Kawamura et al (2018) have found that the WC-type WN phase crystallizes in the structures with unit-cell parameters of a = 2.898 and c = 2.831 A ˚, and a = 2.822 A ˚and c = 2.789 A ˚; the bulk moduli were determined to be 383 and 342 GPa, respectively. The calculated bulk moduli shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…42 Tungsten atoms in the U 7 Te 12 -type W 7 N 12 exist in 8-and 9-fold coordination by nitrogen. Reported tungsten nitrides, which were synthesized below 10 GPa, such as WC-type WN, 23 r-W 2 N 3 , 21 and the starting sample of MoC-type WN 0.6 , 24 have a lower coordination number (CN) of 6 (Figure S7). U 7 Te 12 -type W 7 N 12 is considered to have a higher coordination number, because it was synthesized at a higher pressure of 70 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…The starting material used in this experiment follows the instructions described by Sasaki and colleagues in ref . The nitridation of tungsten was carried out by using a DIA-type cubic multianvil large volume press installed at Nagoya University.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation